THE INFLUENCE OF PROFITABILITY AND ACTIVITY RATIOS ON THE SHARES MARKET PRICE OF THE PUBLIC BANK COMPANIES IN INDONESIA - Dwidjosumarno, Bambang Hadi Santoso (Faculty of Business, Widya Mandala Catholic University Surabaya, Indonesia, 2019)
The purpose of the study is to examine the influence of the ratios of ROA, ROE and ROI altogether and each of them and the shares market price of public bank companies in Indonesia during 2012-2017. ROA and ROE ratios on this study are regarded as the proxy of profitability ratios, while, ROI ratio on this study is considered as the proxy of activity ratio. Based on the study result, it shows that all ratios have a positive relationship with the shares market price of public bank companies in Indonesia. The results exhibit that each ROE and ROI has a positive relationship with the shares market price of public bank companies in Indonesia. However, it is inconsistent with ROA that it found that there is no relationship between ROA and the shares market price of public bank companies in Indonesia